Adapting Engineering to the Hydrogen Economy - RHYS WILLIAMS (2022)
This thesis investigated the possibility of Unitbirwelco expanding its current business activities to be more hydrogen focussed. With the aim of providing a document that the company could use to provide insight and reinforce decision making about investment into the hydrogen in-dustry. Some of the best hydrogen sectors for Unitbirwelco include hydrogen pressure vessels and hydrogen base pilot flames for their flare stacks. Unitbirwelco is an engineering company with over 100 years of engineering experience which allows them to adapt their current prod-ucts to support hydrogen and grow their business in this thriving industry.Hydrogen has many engineering challenges from production, storage, transportation, and uti-lization. Each of these areas is broken down into chapters with potential hydrogen products. Production of hydrogen requires many processes to be used effectively. Some of these pro-cesses Unitbirwelco is already involved with such as Hydrogen dehydration.The storage of hydrogen provides the best opportunity for Unitbirwelco to expand its expe-rience in this rapidly growing market. Type 1 and 2 tanks are produced using metals which the company has excellent knowledge of. However, the market is pushing for lighter, higher volume pressure vessels which require filament winding technologies, a fabrication method the company has little experience using.Transportation of hydrogen is achieved through four main methods, pressure vessels, tube trailers, pipelines and liquid hydrogen tankers. The tube trailer market would allow Unit-birwelco to use its fabrication knowledge to produce frames used to store hydrogen pressure vessels.The utilization of hydrogen provides both internal and external hydrogen uses. There are opportunities for Unitbirwelco to expand into consumer markets with hydrogen boilers and all-in-one systems, while also providing options to reduce their own emissions. Unitbirwelco has many different opportunities to expand into the hydrogen economy and in-vesting to adapt their current products to utilize the fuel would provide them with the oppor-tunities to be successful in the future.